2021
DOI: 10.1002/evl3.262
|View full text |Cite
|
Sign up to set email alerts
|

Pollinators and herbivores interactively shape selection on strawberry defence and attraction

Abstract: Tripartite interactions between plants, herbivores, and pollinators hold fitness consequences for most angiosperms. However, little is known on how plants evolve in response—and in particular what the net selective outcomes are for traits of shared relevance to pollinators and herbivores. In this study, we manipulated herbivory (“presence” and “absence” treatments) and pollination (“open” and “hand pollination” treatments) in a full factorial common‐garden experiment with woodland strawberry ( Frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 59 publications
(142 reference statements)
0
14
0
Order By: Relevance
“…Where interactions involving mutualists and antagonists are mediated by the same trait in plants, rarely are pollinators implicated as predominant selective agents [63]. This study, therefore, represents the first evidence, to our knowledge, of pollinator-mediated selection acting on a defence-related compound in nectar.…”
Section: Discussionmentioning
confidence: 90%
“…Where interactions involving mutualists and antagonists are mediated by the same trait in plants, rarely are pollinators implicated as predominant selective agents [63]. This study, therefore, represents the first evidence, to our knowledge, of pollinator-mediated selection acting on a defence-related compound in nectar.…”
Section: Discussionmentioning
confidence: 90%
“…In response to the damage caused by herbivorous insects, plants have evolved both direct defenses (e.g., chemical compounds and physical barriers) and indirect defenses (e.g., volatile organic compounds, VOCs) that attract—or enhance the effectiveness of—herbivores’ natural enemies ( Kessler and Baldwin, 2002 ; Poelman et al, 2008 ; Mithöfer and Boland, 2012 ). Furthermore, defensive traits may also attract or repel pollinators ( Galen and Cuba, 2001 ; Ramos and Schiestl, 2020 ; Egan et al, 2021 ). Defensive traits can thus affect herbivores, their natural enemies, and pollinators ( Bukovinszky et al, 2008 ; Poelman et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Defensive traits can thus affect herbivores, their natural enemies, and pollinators ( Bukovinszky et al, 2008 ; Poelman et al, 2008 ). Recent evidence has shown that pollinators are also important selective agents of both plant defensive and reproductive traits ( Herrera et al, 2002 ; Strauss and Irwin, 2004 ; Kessler and Halitschke, 2009 ; Kessler et al, 2011 ; Adler et al, 2012 ; Campbell and Kessler, 2013 ; Muola et al, 2017 ; Ramos and Schiestl, 2019 , 2020 ; Rusman et al, 2019 ; Santangelo et al, 2019 ; Egan et al, 2021 ; Table 1 ). For instance, plants profit from large, colorful flowers that attract pollinators, but such attractive signals sometimes also attract herbivores, imposing an ecological trade-off on the signals’ evolution ( Ramos and Schiestl, 2019 ; Egan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations